Factors Associated With Increased Prevalence of Diabetic Foot Ulcer and its Poor Outcome (Medical Forum Monthly, 2024)
in our set up Study Design: Observational / prospective study Place and Duration of Study: This study was conducted at Bahawalpur Victoria Hospital, Bahawalpur from December 2015 to February 2016. Materials and Methods: One hundred and one patients above the age of 18 years presenting with DFU were enrolled. Detailed history was taken regarding patient’s education, type and duration of diabetes, smoking and comorbids like hypertension and ischemic heart disease(IHD). We evaluated ulcer for duration, site, pain and depth of wound. Results: Majority of patients were male(69.3%), had type 2 Diabetes(95%) and were uneducated(82.17%). Mean age was 59±10.43 years and mean duration of diabetes was 10.38±7.9 years. 32.6% patients had Hypertension, 23.7% had IHD and 24.7% were smokers. 85.1% had sensory neuropathy and 41.58% had retinopathy. PAD(18.8%) and nephropathy(7.9%) were relatively uncommon. Patients were divided into three groups based on outcome: healed(2.97%), unhealed(63.36%) and amputation(33.66%) group. Mean duration of presentation was 24±10.39 days in healed, 72.61±179.49 days in unhealed and 49.82±41.75 in amputation group. Wagner classification showed that 0% in healed, 70.31% in unhealed and 94.11% ulcers in amputation group were of grade 3 or above. Sensory neuropathy (94.11%) and smoking(29.41%) were more common and mean HbA1c(8.05±1.55) was highest in amputees. Conclusion: DFU is common in old, uneducated males with long duration of Diabetes. Hypertension, IHD, neuropathy, retinopathy and smoking were common in DFU patients. PAD and nephropathy were uncommon. We observed high amputation and low healing rates. Sensory neuropathy, wagner grade (p values <0.05), poor glycemic control and smoking (p values >.05) were associated with poor outcome. Earlier presentation and aggressive treatment according ulcer grade can improve outcome of this disabling morbidity.